Rhombencephalitis in cocaine-induced nasal septal perforation and skull base erosion. Issue 1 (2nd January 2019) - Li, Shuo; Garg, Gunjan; Goyal, Bobby; Abdelbaki, Ahmed; Hegde, Rahul; Kumar, Anil; Rosovsky, Mark
Abstract: Rhombencephalitis is a rare and potentially fatal condition involving the brainstem, with infectious, autoimmune, and paraneoplastic etiologies. We present a patient presenting with left-extremity weakness and dysphonia who had brainstem imaging findings suggestive of rhombencephalitis. We suspect that the case was due to inoculation of the brainstem from nasopharyngeal adenoviral infection. Due to heavy cocaine use, extensive basiocciput erosion led to direct contact between the brainstem and the nasopharyngeal mucosa. The patient's milder clinical course might have been due to some degree of pre-existing immunity against adenovirus. Additionally, clinicians need to be aware of the proximity of the brainstem to the nasopharynx when there is basiocciput erosion, due to the potential risk of injury during instrumentation.